2001
DOI: 10.1046/j.1444-2906.2001.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence of kingfish from Japan, Australia and New Zealand inferred by microsatellite DNA and mitochondrial DNA control region markers

Abstract: Genetic polymorphism in kingfish, collected from coastal waters of Japan, Australia and New Zealand, were examined using microsatellite (MS) DNA and mitochondrial DNA (mtDNA) control region markers. Sixteen to 25.7 alleles per locus were observed in three MS markers, while the average observed (and expected) heterozygosities were 0.782 (0.918), 0.750 (0.809) and 0.650 (0.888) for Australian, Japanese and New Zealand kingfish, respectively. Twelve mtDNA haplotypes were detected by the digestion of control regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
23
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 15 publications
4
23
1
1
Order By: Relevance
“…Among them, the mitochondrial DNA (mtDNA) control region has been used widely to investigate both population genetic structure and variability because of its rapid evolutionary rate (Nyakaana et al 2002;Sato et al 2004;Chen et al 2006). The analysis of the mtDNA control region is a frequently used method to estimate genetic differentiation between populations, population history with haplotype distribution, and intraspecific phylogeography in fish (Nugroho et al 2001;Grunwald et al 2002;Zhao et al 2009). In the present study, we analyzed the mtDNA control region to estimate population genetic diversity and genetic structure of elongate loach inhabiting the upper reaches of the Yangtze River in China.…”
mentioning
confidence: 99%
“…Among them, the mitochondrial DNA (mtDNA) control region has been used widely to investigate both population genetic structure and variability because of its rapid evolutionary rate (Nyakaana et al 2002;Sato et al 2004;Chen et al 2006). The analysis of the mtDNA control region is a frequently used method to estimate genetic differentiation between populations, population history with haplotype distribution, and intraspecific phylogeography in fish (Nugroho et al 2001;Grunwald et al 2002;Zhao et al 2009). In the present study, we analyzed the mtDNA control region to estimate population genetic diversity and genetic structure of elongate loach inhabiting the upper reaches of the Yangtze River in China.…”
mentioning
confidence: 99%
“…Kingfish are distributed in temperate waters around New Zealand, Australia, Japan, South Africa, and the west coast of the United States. Three geographically separate populations, or subspecies, are thought to occur: S. lalandi dorsalis, off California; S. lalandi aureovittata, in Asian waters; and S. lalandi lalandi, in the Southern Hemisphere (Fisheries Research Institute 1998), although a recent study observed significant genetic divergence between kingfish populations from Japan and those from AustraliaNew Zealand (Nugroho et al 2001). Kingfish are distributed throughout New Zealand waters from the Kermadec Islands and Three Kings Islands in the north, to Cook Strait in the south, and east to the Chatham Islands.…”
Section: Introductionmentioning
confidence: 97%
“…Within the mtDNA, since the control region has been shown to evolve five times faster than coding regions, it is suitable for assessing intraspecific genetic variation (Moritz et al, 1987;Meyer, 1993). Nowadays, analysis of the mtDNA control region is a frequently used method to resolve genetic differentiation, population structures, haplotype distribution, and intraspecific phylogenesis in fish (Nugroho et al, 2001;Grunwald et al, 2002;Guarniero et al, 2002;Sato et al, 2004). Assuming that Schizopygopsis c. baoxingensis is a subspecies only occurring in a single population, it is very important to investigate its genetic background while it is still abundant in the wild.…”
mentioning
confidence: 99%